Fault diagnosis in rotating machinery using pattern recognition technique / Nor Azlan Othman, Nor Salwa Damanhuri and Visakan Kadirkamanathan - Othman, Nor Azlan; Damanhuri, Nor Salwa; Kadirkamanathan, Visakan (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2009)
This paper presents a detail review of fault diagnosis in rotating machinery. Pattern recognition technique which needs three mean steps of fault diagnosis -feature extraction, dimensionality reduction and fault classification – was used. This paper focuses on the faulty bearing which is mainly caused by mass imbalance and axis misalignment. By analyzing the vibration signal obtained from the test rigs (rigs that are built to demonstrate the effect of faults in rotating machinery), it gives solid information concerning any faults within the rotating machinery.